A study on the rights of foreign domestic workers in Malaysia: a legal perspective / Faten Ellyni Md Yasin and Natasha Azmi - Md Yasin, Faten Ellyni; Azmi, Natasha (2008)
This project paper is focus on the rights of foreign domestic workers in Malaysia. As there is tremendous rising on the population of foreign domestic workers in Malaysia, there is a need to look at the protection of their rights. Series of abuse and lack of protection highlighted in mass media shows that Malaysia has fail to uphold their rights and its gives an impression that Malaysia is not sensitive to the issue of human rights. Thus there is a chance to the employer to become abusive. The main issue here is the lack of provisions or specific law implemented to govern foreign domestic workers. Another issue discussed is the type of abuse imposed on the foreign domestic workers and comparison of the treat by Malaysian citizens and the government towards foreign domestic workers with other countries. It is submitted that the execution of such law is needed to increase the effectiveness of the management of foreign domestic workers in Malaysia. One way to do it is by increasing the co-ordination between sending and receiving countries. Through proper co-ordination, then only the rights of these workers are protected and various problems can be resolved.